2023
DOI: 10.1109/access.2022.3232984
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Machine Learning in Identifying Students At-Risk and Minimizing Failure

Abstract: Education is very important for students' future success. The performance of students can be supported by the extra assignments and projects given by the instructors for students with low performance. However, a major problem is that students at-risk cannot be identified early. This situation is being investigated by various researchers using Machine Learning techniques. Machine learning is used in a variety of areas and has also begun to be used to identify students at-risk early and to provide support by ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Hybrid deep learning models enhance the modelling process in terms of computation, functionality, resilience, and accuracy. From the major works listed in Table 2, the significant performance is resulted in [34,40,45,50,53]. These studies show that the performance accuracy of the models can be very high, though it depends on the dataset quality.…”
Section: Critical Review Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid deep learning models enhance the modelling process in terms of computation, functionality, resilience, and accuracy. From the major works listed in Table 2, the significant performance is resulted in [34,40,45,50,53]. These studies show that the performance accuracy of the models can be very high, though it depends on the dataset quality.…”
Section: Critical Review Of Resultsmentioning
confidence: 99%
“…Prediction of at-risk students [31,32,34,65,38,40,41,42,52,67,63,66,62,60,90,91,61,58,59,64] 20 Features affecting the academic performance [76,36,39,43,44,79,70,77,51,81,80,69,83,74,82,78,84,92,68,85,75,71,93,72] 24 Suitable Course selection [87,86,55,88,89,48] 6 Prediction of marks / grades [29,30,37,45,46,47,94,49,50,53,95,96,62,90,97,98,58,99,100,16,72,9 8,18,15,75,101,102,64]<...…”
Section: Idmentioning
confidence: 99%
“…This method utilized a genetic algorithm to capture the 30 best attributes from students' historical learning data and trained a K-NN regression model and a decision tree using these features and labels to predict students' performance score and categories. PEK et al [16] used naive Bayes, random forest, decision tree, AdaBoost classifier, logistic regression, and KNN algorithms as basic learners, support vector machine (SVM) as meta-learner, and created a stacking method to develop a hybrid ensemble model. By analyzing the data, they discovered important features that influence student learning outcomes and successfully helped teachers identify students at risk.…”
Section: Related Workmentioning
confidence: 99%
“…The number of records assessed for eligibility was 709. After screening, highly relevant studies were identified (n = 50) (Adnan et al, 2021(Adnan et al, , 2022Alamri & Alharbi, 2021;Alhazmi & Sheneamer, 2023;Aljaloud et al, 2022;Alshanqiti & Namoun, 2020;Asthana et al, 2023;Bujang et al, 2021;Chan et al, 2023;Chui et al, 2020;Feng et al, 2022;Gao et al, 2019;Ghorbani & Ghousi, 2020;Hassan et al, 2022;Hussain et al, 2021;Kastrati et al, 2020;Kusumawardani & Alfarozi, 2023;Latif et al, 2023;Liu et al, 2020;Mengash, 2020;Motz et al, 2021;Munshi & Alhindi, 2021;Nabil et al, 2021;Nguyen-Huy et al, 2022;Okoye et al, 2023;Orlando et al, 2020;Pek et al, 2023;Prabowo et al, 2021;Rafique et al, 2021;Rahman et al, 2021.…”
Section: Search Strategymentioning
confidence: 99%